Process Modelling And Control Of Isoamyl Acetate Synthesis In Microreactor Using Matlab Simulink - Elysia Chiang, Chern Yuen (Universiti Sains Malaysia, 2018)
Isoamyl acetate is an ester that exhibits banana-like flavour. As demand for food flavour industry and banana flavouring have risen this recent years, enzymatic esterification has been found to be a natural-labelled alternative to produce isoamyl acetate. Continuous process based on microreactor technology has been given focus in biochemical process as they offer a less wasteful process compared to traditional methods. The objective of this study is to develop a control strategy to optimize the ester yield by using step test, Ziegler Nichols and Cohen-Coon methods. Before process control was carried out, the process model from MATLAB script was translated into Simulink blocks. Simulation was carried out in MATLAB Simulink and the proposed model was validated with experimental work and previous simulation result using EXCEL Solver. PID with P, I and D values of 6.8, 0.56 and 0.14 respectively were found to be the best controller in term of performance criteria such as overshoot, rise time, time to first peak, settling time, decay ratio and response curve.